(untitled) (Journal of Plant Disease Sciences, 2025)
Pigeon pea (Cajanus cajan (L.) Millsp.) is a major legume crop cultivated extensively in rainfed semi-arid regions and plays a vital role in India’s pulse production. However, Fusarium wilt (Fusarium udum) is a major constraint, causing significant yield losses.This study aimed to assess the performance of different pigeon pea varieties for wilt resistance and yield potential through on-farm demonstrations in Vijayapur district, Karnataka, over two cropping seasons (2019–20 and 2020–21).